Microbiological Effect of Cold Chain Temperature Simulation and Thawing Methods in Chicken Tenders - Santos L., Guillermo Y. (Zamorano: Escuela Agrícola Panamericana, 2024)
In this study, three storage temperatures-4 °C, -10 °C, and -20 °C for fridge (FD), freezer (F), and blast freezer (BF), respectively, as well as two thawing techniques for chicken tenders stored at two freezing temperatures (-10 °C and -20 °C) were used to examine the microbiological effects of temperature fluctuations in the cold chain. Three microbiological indicators, aerobic mesophilic bacteria (AMB), enterobacteriaceae (EB), and psychrotrophs (PSY), were counted using the Tempo® enumeration method. In the simulation study, the three microorganisms in FD had a rising tendency, but in the F and BF storages, AMB and EB displayed a steadier behavior, except for PSY, which displayed an increasing pattern. PSY were the ones with the greatest counts throughout all three storage types, although at BF temperatures, their numbers dropped before stabilizing. Contrarily, AMB and EB had the lowest numbers throughout all storages, although they showed an increased tendency in FD and a downward and steady trend in F and BF. The results regarding thawing methods revealed irregular patterns. In the case of BF and F storage, the initial (frozen) counts exhibited the highest numbers for AMB and PSY. Conversely, for the Fridge (24 H) thawing method, it showed the lowest counts for EB and PSY, but AMB had the lowest counts compared to Counter (6 H) thawing, where AMB counts were the highest. However, Counter (6 H) had lower counts for AMB but higher counts for EB, and Fridge (24 H) showing lower PSY counts, but higher for EB and AMB.